Beyond pulmonary nontuberculous mycobacteria disease: do extra-pulmonary forms represent an emerging clinical and public health threat?. Issue 3 (19th September 2017) - Biondi, Gabriele; Sotgiu, Giovanni; Dore, Simone; Molicotti, Paola; Ruggeri, Melania; Aliberti, Stefano; Satta, Rosanna
Nontuberculous mycobacteria (NTM) are a heterogeneous group of pathogens including all mycobacteria other than Mycobacterium tuberculosis complex and Mycobacterium leprae [1]. The rate of NTM infection has increased substantially over the last decades, especially in high-income countries, as recently illustrated by Diel et al. [2] who have highlighted the relevant clinical and economic burden of NTM disease in Germany. The main reasons include the aging of the population, the increasing number of patients with immunodepressive disorders, the use of immunosuppressive agents and a substantial increase in awareness of the disease [3]. Epidemiological data on NTM worldwide are lacking and very few reports have been published based on the Italian population [4, 5]. Pulmonary and extra-pulmonary diseases caused by nontuberculous mycobacteria: new clinical and public health threats http://ow.ly/87Dm30eMFd9